Basal ganglia for beginners: the basic concepts you need to know and their role in movement control - Rocha, Gabriel S.; Freire, Marco A. M.; Britto, André M.; Paiva, Karina M.; Oliveira, Rodrigo F.; Fonseca, Ivana A. T.; Araújo, Dayane P.; Oliveira, Lucidio C.; Guzen, Fausto P.; Morais, Paulo L. A. G.; Cavalcanti, José R. L. P. (Frontiers in Systems Neuroscience, 2023)
The basal ganglia are a subcortical collection of interacting clusters of cell bodies, and are involved in reward, emotional, and motor circuits. Within all the brain processing necessary to carry out voluntary movement, the basal nuclei are fundamental, as they modulate the activity of the motor regions of the cortex. Despite being much studied, the motor circuit of the basal ganglia is still difficult to understand for many people at all, especially undergraduate and graduate students. This review article seeks to bring the functioning of this circuit with a simple and objective approach, exploring the functional anatomy, neurochemistry, neuronal pathways, related diseases, and interactions with other brain regions to coordinate voluntary movement.Movement is an essential ability to maintain life. Even fewer complex beings such as bacteria need to move in search of nutrients and ensure their survival (Lodish et al., 2021). In humans, movement goes beyond locomotion and involves a myriad of important aspects, such as object manipulation, verbal communication, feeding and vision, since we need eye movements to search for and maintain in visual focus anything that is the target of our attention (Bear et al., 2020). Voluntary movement is prepared and initiated in the motor cortex; such preparation mainly involves corticothalamic projections, while the initiation of motor action consists of corticospinal projections